1996
DOI: 10.1111/j.1399-0039.1996.tb02513.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel alleles HLA‐B*7802 and B*51022: evidence for convergency in the HLA‐B5 family

Abstract: We have characterized two novel HLA-B alleles, B*7802 and B*51022. The Caucasian-derived variant B*7802 most resembles the African-derived variant B*7801, from which B*7802 differs by two nucleotides. Only one of these modifications, however, is translated: a tyrosine for aspartate substitution occurs at residue 74 in B*7802, while the second nucleotide difference reflects a proximal synonymous substitution in codon 23. A second variant, B*51022, differs synonymously only at codon 23 from B*51021. Comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The major peptide motifs of B*3905, that is His2 and Leu9, are also found in a few other HLA-B allotypes: B*3901, B*3909, B*1509, B*1510, and B*3801 (24,18,25). Of the 25 peptides sequenced from B*3905, 6 (24%) were previously sequenced from B*3901 (18)(19)(20), 3 (12%) from B*3909 (19,20), 2 (8%) from B*3801 (18), 4 (16%) from B*1509 (24), and 1 (4%) from B*1510 (25). Due to the limited number of peptides sequenced from any one allotype the percent sharing observed is probably a minimum one.…”
Section: Discussionmentioning
confidence: 91%
“…The major peptide motifs of B*3905, that is His2 and Leu9, are also found in a few other HLA-B allotypes: B*3901, B*3909, B*1509, B*1510, and B*3801 (24,18,25). Of the 25 peptides sequenced from B*3905, 6 (24%) were previously sequenced from B*3901 (18)(19)(20), 3 (12%) from B*3909 (19,20), 2 (8%) from B*3801 (18), 4 (16%) from B*1509 (24), and 1 (4%) from B*1510 (25). Due to the limited number of peptides sequenced from any one allotype the percent sharing observed is probably a minimum one.…”
Section: Discussionmentioning
confidence: 91%
“…The high frequency of B*5301 supports the idea that alleles can be positively selected under pathogenic pressure (19). HLA‐B78 was previously thought to be African restricted (12, 20), but recent studies have shown that subtypes of this antigen are found in native Americans, caucasians, Hispanics and Orientals as well (18, 21–24).…”
mentioning
confidence: 99%
“…Similar nucleotide substitutions have been reported between B*53 and B*35 (11) or B*38 and B*39 (12). Based on the previously described hypothesis (4, 13), it is likely that B*7805 is formed from B*52011 by a gene conversion from Bw4 to Bw6 in the coding region defining Bw4/6. HLA‐B52 is a common class I antigen in various ethnic groups and its high frequencies are observed in Japanese (10.7%) (14), whereas the allele frequency of B*78 is very rare in Japanese and geographically localized in Senegale (5.2%), West Africa (1.4%), Kazakhstan (0.8%) (14) and Venezuela (0.022%) (15).…”
Section: Pcr and Sequencing Primers In This Studymentioning
confidence: 94%
“…The first B78 allele was B*7801 found in Moroccans as B’SNA’ (1, 2). While B*7801 was associated with black populations (3), B*78021 (4), B*78022 (5) and B*7803 (C. Hurley, unpublished data) have been identified in Caucasian populations, and recently B*7804 has been detected in Hispanic populations (6).…”
Section: Pcr and Sequencing Primers In This Studymentioning
confidence: 99%